Characterization of humic acids from a Brazilian Oxisol under different tillage systems by EPR, C-13 NMR, FTIR and fluorescence spectroscopy - Gonzalez Perez, M.; Martin-Neto, L.; Saab, S. C.; Novotny, E. H.; Milori, DMBP; Bagnato, V. S.; Colnago, L. A.; Melo, W. J.; Knicker, H. (Elsevier B.V., 2004)
The importance of soil organic matter functions is well known, but structural information, chemical composition and changes induced by anthropogenic factors such as tillage practices are still being researched. In the present paper were characterized Brazilian humic acids (HAs) from an Oxisol under different treatments: conventional tillage/maize-bare fallow (CT1); conventional tillage/maize rotation with soybean-bare fallow (CT2)-, no-till/maize-bare fallow (NT1); no-till/maize rotation with soybean-bare fallow (NT2); no-till/maize-cajanus (NT3) and no cultivated soil under natural vegetation (NC). Soil HA samples were analyzed by electron paramagnetic resonance (EPR), solid-state C-13 nuclear magnetic resonance (C-13 NMR), Fourier transform intra-red (FTIR) and UV-Vis fluorescence spectroscopies and elemental analysis (CHNS). The FTIR spectra of the HAs were similar for all treatments. The level of semiquinone-type free radical determined from the EPR spectra was lower for treatments no-till/maize-cajanus (NT3) and noncultivated soil (1.74 X 10(17) and 1.02 x 10(17) spins g(-1) HA, respectively), compared with 2.3 X 10(17) spins g(-1) HA for other soils under cultivation. The percentage of aromatic carbons determined by C-13 NMR also decreases for noncultivated soil to 24%, being around 30% for samples of the other treatments. The solid-state C-13 NMR and EPR spectroscopies showed small differences in chemical composition of the HA from soils where incorporation of vegetal residues was higher, showing that organic matter (OM) formed in this cases is less aromatic. The fluorescence intensities were in agreement with the percentage of aromatic carbons, determined by NMR (r = 0.97 P < 0.01) and with semiquinone content, determined by EPR (r = 0.97 P < 0.01). No important effect due to tillage system was observed in these areas after 5 years of cultivation. Probably, the studied Oxisol has a high clay content that offers protection to the clay-Fe-OM complex against strong structural alterations. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: tropical soil; no-till; organic matter; humification degree